2021
DOI: 10.1021/acsami.1c04679
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Visible-Light Photocatalysis via Endohedral Functionalization of Single-Walled Carbon Nanotubes with Organic Dyes

Abstract: The encapsulation of an organic dye, 10-phenylphenothiazine (PTH), in the inner cavity of single-walled carbon nanotubes (SWNTs) as a breaking heterogenization strategy is presented. The PTH@oSWNT material was microscopically and spectroscopically characterized, showing intense photoemission when illuminated with visible light at the nanoscale. Thus, PTH@oSWNT was employed as a heterogeneous photocatalyst in single electron transfer dehalogenation reactions under visible light irradiation. The material showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…In a typical experiment [14], 50 mg of pristine and closed SWNT were suspended in 50 mL of concentrated hydrochloric acid, and the mixture was stirred at 60 °C for 2 h. After cooling down, the solid was isolated by centrifugation and washed with water with the necessary centrifugation cycles till the supernatant reached neutral pH. After drying under vacuum, the procedure yielded the sample oSWNT.…”
Section: Nanotubes Openingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a typical experiment [14], 50 mg of pristine and closed SWNT were suspended in 50 mL of concentrated hydrochloric acid, and the mixture was stirred at 60 °C for 2 h. After cooling down, the solid was isolated by centrifugation and washed with water with the necessary centrifugation cycles till the supernatant reached neutral pH. After drying under vacuum, the procedure yielded the sample oSWNT.…”
Section: Nanotubes Openingmentioning
confidence: 99%
“…The functionalization of SWNT with the photocatalyst has been mainly performed via two different strategies: a) physisorption of the catalyst at the nanotube surface [12] or b) covalent bond between both units [13]. In addition, we also reported a novel functionalization approach, the endohedral functionalization, that consist of the introduction of the photocatalyst, 10-phenylphenothiazine, in the inner cavity of the SWNT [14]. This approach does not require the modification of the photocatalyst to be linked to the material, and we demonstrated that the stability of the photocatalyst is preserved.…”
Section: Introductionmentioning
confidence: 99%
“…), and hybrid processes (Fenton/chemical coagulation, UV/electro-Fenton, membrane/photocatalysis etc. ). Among these, the adsorption process has gained considerable attention because of its simple operation, wide range of applications, cost-effectiveness, high removal capacity, high selectivity, recycling facilities, etc . Considering the factors mentioned above, the present work is focused on the adsorptive removal of cationic methyl green (MG) and anionic Congo red (CR), owing to their excessive use in industrial and biological sectors as well as their ecotoxicological effects. Further, the performance of the adsorbent is determined based on the desired characteristics of an efficient adsorbent, including simple synthesis routes, nontoxicity, high adsorption capacity, and recycling ability .…”
Section: Introductionmentioning
confidence: 99%
“…Following the first reports of filling carbon nanotubes (CNTs) with guest materials 3 decades ago, there has been huge interest in the creation of extremely thin one-dimensional (1D) hybrid materials such as CNTs filled with molecules, other nanotubes, nanowires (NWs) or nanoclusters. One prominent emerging application is the use of CNTs and nanotube heterostructures in photocatalysis, where filled or functionalized nanotubes can boost the rate of photocatalytic redox reactions that remove pollutants, perform CO 2 reduction, or produce hydrogen from water. For such applications, knowledge of the electronic and optical properties of the nanocomposite is vital, in particular because it has reported that the infiltrated material can significantly modify the electronic nature of the outer nanotubes. For example, filling with Te can enhance the charge-carrying capacity of boron nitride nanotubes, growing copper halide nanocrystals inside CNTs can lead to the creation of new carbon-copper energy levels, and filling with alkane can significantly enhance the tunability of the optical performance of CNTs . Further, hybrid nanotube materials,including heterostructures with BN and MoS 2 and other nanotubes, exhibit unique properties such as unconventional Raman signatures, distinct phase transitions, and interesting charge-transfer processes between their constituents. ,, Tremendous developments in liquid-phase separation techniques have enabled the purification of not only the “host” material, such as single-walled carbon nanotubes (SWCNTs), but also nanotube heterostructures based on their metallicity or electronic properties. , Nanotube heterostructures are also attractive components for nanoelectronics, where they can act as functional thermoelectric, photovoltaic, or conductive elements.…”
Section: Introductionmentioning
confidence: 99%